The Effectiveness of Video and Leaflet Media in Increasing Self-Efficacy and Knowledge about HIV/AIDS Prevention - Marisa Lestary Dondo; Nurul Atma Polapa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
HIV/AIDS remains a health problem for adolescents who are vulnerable to risky behaviors due to lack of knowledge and low self-efficacy. This study analyzed the effectiveness of video and leaflet media in improving adolescent self-efficacy and knowledge using a quasi-experimental design with a sample of 254 adolescents divided into two groups. The results showed that both media significantly increased self-efficacy (p=0.000) and knowledge (p=0.000), with the video group showing a greater increase than the leaflet group. Overall, although both videos and leaflets were equally effective, videos proved superior in improving adolescent understanding and confidence regarding HIV/AIDS prevention.